2017
DOI: 10.1126/sciimmunol.aai9297
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by human FOXP3 + regulatory T cells requires FOXP3-TIP60 interactions

Abstract: CD4FOXP3 regulatory T (T) cells are critical mediators of immune tolerance, and their deficiency owing to mutations in immunodysregulation polyendocrinopathy enteropathy X-linked syndrome (IPEX) patients results in severe autoimmunity. Different mutations result in a wide range of disease severity, reflecting the relative importance of the affected residues in the integrity of the FOXP3 protein and its various molecular interactions. We characterized the cellular and molecular impact of the most common IPEX mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…a). Our preclinical results have shown that the allosteric modification of TIP60 improves the FoxP3‐mediated transcriptional program in FoxP3A384T T reg cells, the therapeutic restoration of FoxP3–TIP60 interaction by this small molecule modifier promotes T reg cell function without directly affecting T effector cell responses, and enhances disease protection in mouse models of colitis and collagen‐induced arthritis .…”
Section: Importance Of Foxp3 Interactionsmentioning
confidence: 86%
“…a). Our preclinical results have shown that the allosteric modification of TIP60 improves the FoxP3‐mediated transcriptional program in FoxP3A384T T reg cells, the therapeutic restoration of FoxP3–TIP60 interaction by this small molecule modifier promotes T reg cell function without directly affecting T effector cell responses, and enhances disease protection in mouse models of colitis and collagen‐induced arthritis .…”
Section: Importance Of Foxp3 Interactionsmentioning
confidence: 86%
“…FOXP3 plays an essential role in the maintenance of immunological tolerance to self and innocuous foreign antigens . FOXP3 homodimers can mediate transcriptional regulation through direct binding to DNA, and FOXP3 has also been shown to interact with several molecular partners forming FOXP3/protein complexes that are required for several regulatory processes …”
Section: Discussionmentioning
confidence: 99%
“…For example, acetylation of FoxP3 upon complexing with p300 allows it to evade proteasomal degradation, which constitutes a post‐translational mechanism of FoxP3 stability . Furthermore, we have recently shown that abrogating the FoxP3–Tat‐interacting protein 60 (TIP60) interaction, a defect caused by the germline foxp3 A384T IPEX mutation, relieves human T reg cell suppressive capacity while retaining major aspects of the T reg cell phenotype including the repression of proliferation and inflammatory cytokines . Restoring this interaction using a TIP60 allosteric modifier rescued FoxP3 functions and T reg cell suppressive capacity in vitro and in vivo .…”
Section: Foxp3 the Master Regulator Of Treg Cell Lineage Commitmentmentioning
confidence: 99%
“…R397W and I363V) or interactions with other proteins that aid in orchestrating the T reg transcriptional program (e.g. A384T) . Importantly, the presence of a mutation does not necessarily imply diminished FoxP3 protein expression levels (e.g.…”
Section: Treg Cell Dysfunction In Human Diseasementioning
confidence: 99%